2016
DOI: 10.1007/s00468-016-1430-5
|View full text |Cite
|
Sign up to set email alerts
|

Impact of groundwater depth on leaf hydraulic properties and drought vulnerability of Populus euphratica in the Northwest of China

Abstract: Key message Different groundwater conditions affect leaf hydraulic conductance and leaf pressure-volume parameters in Populus euphratica at the extremely arid zone in the northwest of China. Abstract Efficient water transport inside leaves constitutes a major determinant of plant function, especially in drought-stressed plants. The previous researches have reported the correlation between leaf hydraulic properties and water availability. In this study, we tested the hypothesis that water relation parameters of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 59 publications
2
23
0
Order By: Relevance
“…Drought usually occurs in Northwest China (Pan et al, ; Liu et al, ) and North China (Liu et al, ; Xu et al, ). In recent years, serious droughts in humid Southern China occurred frequently (Xu et al, ; Wu et al, ; Lin et al, ; Wang et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Drought usually occurs in Northwest China (Pan et al, ; Liu et al, ) and North China (Liu et al, ; Xu et al, ). In recent years, serious droughts in humid Southern China occurred frequently (Xu et al, ; Wu et al, ; Lin et al, ; Wang et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Studies found that stem water storage was negatively associated with wood density in five coexisting temperate broad‐leaved tree species (KĂścher, Horna, & Leuschner, ), suggesting the higher water storage as lower wood density. Many studies suggest that most Populus species are highly vulnerable to cavitation causing 50% loss of hydraulic conductivity ( P 50 ) occurring between −1 and −2.5 MPa (Hacke, ; Hukin, Cochard, Dreyer, Le Thiec, & Bogeat‐Triboulot, ; Pan, Chen, Chen, Wang, & Ren, ). For P. euphratica , the basic wood density of stem was less than that of the co‐occurring species, T. ramosissima , 0.41 versus 0.73 g/cm 3 (Yu et al., ), suggesting that P. euphratica can store more water than T. ramosissima .…”
Section: Discussionmentioning
confidence: 99%
“…P. euphratica can improve its water use efficiency accompanied by an increase in hydraulic capacity when it encounters severe water shortage. More specifically, the change in k ll in P. euphratica demonstrated an elastic LSC coincident with a conservative strategy in relatively moderate conditions, and a bolder strategy in relatively extreme conditions [16]. Plants can adapt to challenging conditions using their adaptive functional properties, resulting in the improvement of performance [48,49].…”
Section: Hydraulic Characteristics In Naturally Arid and Severe Drougmentioning
confidence: 97%
“…There is also no evidence for the coordination of water transport capacity among plant organs in P. euphratica. However, research on hydraulic conductance has been generally conducted on sections of specific plant parts (e.g., stems, leaves, shoots) in isolation from each other [16,17]. We know that water supply from roots to leaves depends on the integrity of flow in the xylem [18].…”
Section: Introductionmentioning
confidence: 99%